Molecular biomarkers in metastatic clear cell renal cell carcinoma treated with first-line immune combinations: a systematic review of phase III randomized clinical trials by Meet-URO group - Anna Amela Valsecchi; Michele Maffezzoli; Maria Concetta Cursano; Fabrizio Di Costanzo; Andrea Malgeri; Mattia Alberto Di Civita; Brigida Maiorano; Carlo Messina; Giuseppe Procopio; Davide Bimbatti; Sebastiano Buti; Sara Elena Rebuzzi; et al. (Cancer and Metastasis Reviews, 2026)
Abstract Immune checkpoint inhibitor (ICI)–based combinations represent the standard first-line treatment for metastatic clear cell renal cell carcinoma (mRCC), although robust biomarkers for treatment selection remain undefined. We conducted a systematic review to identify biomarkers assessed in randomized clinical trials (RCTs) on first-line ICI-based regimens. Following PRISMA guidelines, we searched PubMed, Web of Science and Scopus (January 2018–October 2025) for phase III RCTs investigating first-line ICI-based therapies in mRCC with molecular or circulating biomarker analyses. Given heterogeneity across studies, a qualitative synthesis was performed. Sixteen reports were included. Biomarkers were assessed using immunohistochemistry, transcriptomics, genomic sequencing and blood analyses. PD-L1 expression did not reliably discriminate benefit across ICI-based combinations, although it revealed a negative prognostic influence with sunitinib and a potential predictive role for nivolumab-ipilimumab. Tumours with angiogenic signatures were consistently associated with improved outcomes, suggesting prognostic relevance, while derived limited additional benefit from ICIs. Immune-related signatures were associated with ICI response, whereas proliferation and MYC -related signatures identified disease with poor prognosis across treatments. Individual mutations (e.g. PBRM1 , VHL , BAP1 , PTEN ) showed heterogeneous and mainly prognostic associations, whereas composite gene panels (e.g. rDM) may offer better predictive value. Circulating biomarkers, including inflammatory cytokines and KIM-1 dynamics, demonstrated promising prognostic and early predictive signals. No validated biomarker currently supports treatment selection among first-line ICI-based combinations in mRCC. Future research should prioritize adaptive, biomarker-guided trial designs integrating longitudinal multi-omic profiling and circulating biomarkers to generate clinical evidence and support personalized treatments.